2012
DOI: 10.1002/14651858.cd008000.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rheum officinale (a traditional Chinese medicine) for chronic kidney disease

Abstract: In Taiwan, chronic kidney disease (CKD) is highly prevalent and traditional Chinese medicine (TCM) is one of the most commonly used complementary medicines. To date, little information is available on the utilization patterns for TCM among CKD patients, particularly those with late stage CKD. We conducted a cross-sectional hospital-based study to investigate this issue. In this study, late stage CKD patients were identified by ICD-9-CM codes: 585 and 586, and only CKD stage 3b, 4 and 5 patients were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…It also inhibits the activity of K ATP channel and the ion transport (chloride) across colon cells [ 18 ] due to its laxative effect. Rhubarb, a laxative Chinese medical herb since ancient time, has been widely used to reduce uremic toxins for the treatment of CKD in China [ 19 , 20 ]. But it has been used more often via colonic administration than via oral administration since early 1950s [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also inhibits the activity of K ATP channel and the ion transport (chloride) across colon cells [ 18 ] due to its laxative effect. Rhubarb, a laxative Chinese medical herb since ancient time, has been widely used to reduce uremic toxins for the treatment of CKD in China [ 19 , 20 ]. But it has been used more often via colonic administration than via oral administration since early 1950s [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multicenter randomized controlled clinical trials have shown that CHM therapy improves estimated glomerular filtration rate (eGFR) in both patients with stage 3chronic kidney disease (CKD) and idiopathic membranous nephropathy [ 13 , 14 ]. Many CHM preparations have been used in treating CKD in China, and systematic reviews have shown that some are effective [ 15 , 16 ]. Investigations on CHM treatment of DKD have been undertaken in China.…”
Section: Introductionmentioning
confidence: 99%
“…Based on TCM theory, renal failure is due to "deficient functioning of the spleen and kidney", "interior accumulation of dampness and turbidity", and "accumulated poison gathered in the kidney". It is characterized as one of the "consumptive diseases" [8]. Center on 61 patients with CRF revealed that the overall response rate of Jianshen Granules was 85.24%.…”
Section: Introductionmentioning
confidence: 99%